RF CMOS power amplifier class C for wireless communication / [compact disc] - 372658 Azdiana Md. Yusop (Skudai: Universiti Teknologi Malaysia, 2003)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik Elektronik)) - Universiti Teknologi Malaysia, 2003